Mechanical Properties of Luffa Fiber Reinforced Recycled Polymer Composite - Nicholas Kuan, Hoo Tien; Mohd Khairul, Afiq; Scollastica Jane, Lumpong (Trans Tech Publications Ltd., 2024)
Environmental issues over the eventual fate of post-consumer polymers can be dealt with in two separate ways which is recycling or using biodegradable polymers. However, it is evident that recycling polymers from post-consumer polymers can decrease the mechanical properties over time. Hence, to strengthen the recycled polymers, integrating fibers, such as luffa, into the High-Density Polyethylene (HDPE) matrix, was carried out to produce a fiber reinforced recycled polymer (FRrP) composite. The tensile testing of the FRrP composite shows that the 10% fiber volume fraction (FVF) composite exhibits a higher tensile strength of 3.9% than the neat recycled HDPE (RHDPE). In terms of Young’s Modulus, the 5% FVF of FRrP is shown to have a higher value than the neat RHDPE by 54%. The low density of luffa fibers also contributes to the composites lightweight character. The impact testing shows that the FRrP enhances the impact properties when compared to the neat RHDPE. The peak load, perforation energy, and the total energy absorbed by the FRrP indicate an increasing trend when luffa, of up to 15% FVF, is added as the reinforcement. Thus, the addition of luffa as reinforcement in RHDPE shows significant potential as a high-performance, sustainable, and environmentally friendly material, such as automotive parts and protective gear.